Prevalence and Factors Associated With Postural Abnormalities in Male Students of Tehran Universities: A Cross-sectional Study - Shehada, Mohammed Said; Karimi, Noureddin; Baraghoosh, Parastoo; Mohammadi, Fariba; Ahmadi, Amena (Physical treatments, 2023)
Purpose: Postural abnormalities, such as forward head posture (FHP), posterior kyphosis, and lumbar lordosis, can lead to discomfort and health problems. This cross-sectional study was conducted to investigate the prevalence of these abnormalities and their association with age, body mass index (BMI), and physical activity among male students of Tehran universities. Methods: A cross-sectional study was conducted on 400 students of Tehran University of Medical Science to evaluate the relationship between postural abnormalities and associated factors. Participants’ demographic data and physical activity levels were collected using questionnaires, and spinal curvature was assessed using a spinal mouse device and photogrammetry. Statistical analysis was performed using IBM SPSS software, version 22, and a Pearson correlation coefficient was used to examine the relationship between variables. Results: The study revealed a high prevalence of postural abnormalities, with FHP being the most prevalent (84.5%), followed by lumbar lordosis (79.8%), and posterior kyphosis (34.7%). Factors, such as age, BMI, waist-to-hip ratio, and physical activity were significantly associated with the occurrence of postural abnormalities. Conclusion: A study on male university students showed that FHP, posterior kyphosis, and lordosis are common postural abnormalities with varying degrees of occurrence. FHP was the most prevalent type of abnormality. Age and BMI were correlated with the prevalence of postural abnormalities, and kyphosis was more common among younger students. BMI was also significantly related to the prevalence of postural abnormalities, and physical activity was associated with the prevalence of FHP.